Analisis Nilai Impor Menurut Golongan Standard International Trade Classification (SITC) di Indonesia Tahun 2010-2021 - Trie Hierdawati; Amrizal amrizal; Rian Dani (Universitas Batanghari, 2022)
This study aims to see the Development of Import Values According to the Standard International Trade Classification (SITC) in Indonesia in 2010-2021 which has an average of 4.56% with an average import value of 166,890 (Million US) where the value of The highest import growth occurred in 2011 at 30.79% with the import value increasing by 177,436 (Million US) when compared to 2010 at 135,663 (Million US) while the lowest import growth value occurred in 2015 at -19 ,91% with the value of imports decreased by 142,695 (Million US) when compared to the previous year 2014 of 178,179 (US million). Contribution of Imported Product Value According to the Standard International Trade Classification (SITC) in Indonesia in 2010- 2021 it was found that the contribution of imported food products and live animals was 8.71% for Beverages and Tobacco by 0.45% for Foodstuffs. raw materials, not to be eaten by 5.27% for pelican fuel, polishing materials and other related materials by 18.24% for fats and animal and vegetable oils by 0.11% for chemicals by 13 ,93% for factory-made goods broken down by material by 15.99% for Machinery and transportation equipment by 32.07% for various types of factory-made goods by 4.67% and for goods transactions not broken down by 0.57 %.